An adaptive approach to define thermal comfort zones on psychrometric chart for naturally ventilated buildings in composite climate of India. (15th November 2016) - Kumar, Sanjay; Mathur, Jyotirmay; Mathur, Sanjay; Singh, Manoj Kumar; Loftness, Vivian
Abstract: Thermal comfort standards such as ASHRAE 55-2013 defines comfort boundaries which are based on the experimental results conducted in climatic chambers and field studies. The current comfort standards do not reflect the cultural and climatic diversity of India. A thermal comfort field study was conducted in 32 naturally ventilated buildings, collecting a total of 2610 samples spread over a total period of four years, covering all seasons, wide age groups, clothing types, and building types. In the present study, ASHRAE comfort boundaries at three different air speeds - still air (up to 0.2 m/s), natural air flow (0.2 m/s–0.5 m/s) and forced air flow with ceiling fan assist (0.5 m/s–1.5 m/s) are investigated. The method of calculation suggested by the ASHRAE 55-2013 and ISO-7730 were followed to determine extended acceptable temperature ranges for comfort at elevated air speed. Comfort boundaries are defined based on climate specific adaptations, the role of air speed and thermal preferences. Results from this study indicate that subjects in naturally ventilated buildings of this region are comfortable at temperatures different from those suggested by ASHRAE 55 and ISO-7730 standards. New extended boundaries of comfort zones are proposed considering various adaptations specific to this region, including the role of air speed to offset the temperature. The proposed comfort zones show that subjects are comfortable up to 32 °C at still air condition (0 m/s–0.2 m/s) and up to 35 °C at higher speed (up to 1.5 m/s) in naturally ventilated buildings in the composite climate of India. Highlights: About 82% of the subjects found comfortable at prevailing indoor conditions in present study. Applicability of ASHRAE 55 comfort zones at elevated air speed is evaluated. Study reveals that comfort zones are dependent on climatic specific adaption and comfort expectations. Study proposes new boundaries of comfort zones using adaptive comfort approach.